(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The views of modern Russian writers D. Bykov, A. Melikhov, Z. Prilepin on the personality and work of M. Sholokhov are presented. The features of their reading of the writer’s works are considered, the diversity and inconsistency of assessments and opinions are emphasized. Particular attention is paid to the attitude of modern writers to the problem of authorship of the novel «And Quiet the Don Flows». The analysis showed that all of the above authors emphasize the connection of the novel-epic M. Sholokhov with previous and subsequent works of the writer. But, if A. Melikhov and Z. Prilepin completely deny the fact of plagiarism, D. Bykov admits the fact of partial borrowing. Key words: M. Sholokhov, D. Bykov, A. Melikhov, Z. Prilepin, «And Quiet the Don Flows», “Virgin Soil Upturned», image of the writer, problem of authorship. DOI 10.18522/1995-0640-2020-1-21-26